2022
DOI: 10.1155/2022/5298530
|View full text |Cite|
|
Sign up to set email alerts
|

Design and Implementation of Tourism Teaching System Based on Artificial Intelligence Technology

Abstract: The tourism teaching system provides all kinds of teaching resources for students and shares good teachers, which greatly improves the quality of teaching and learning, and it enables students to teach and learn randomly in the system. The mode of educational information dissemination has also changed, resulting in great changes in educational models, ideas, and methods. The tourism teaching system overcomes the shortcomings of traditional education. In the 21st century, the means of education and teaching wil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…This is one area to explore further and identify the potential avenues to expand. Xing (2022) states that "AI is a technical science integrating multiple disciplines. The system can realize the interaction in the front, back, left, right, up, and down directions in tourist attractions through control equipment, such as the keyboard, mouse, or joystick.…”
Section: How To Deal With Ai Challenges In Education?mentioning
confidence: 99%
“…This is one area to explore further and identify the potential avenues to expand. Xing (2022) states that "AI is a technical science integrating multiple disciplines. The system can realize the interaction in the front, back, left, right, up, and down directions in tourist attractions through control equipment, such as the keyboard, mouse, or joystick.…”
Section: How To Deal With Ai Challenges In Education?mentioning
confidence: 99%
“…Producing exam pattern paper is an integral aspect of the English education infrastructure since it encourages students to study on their own time. Research by Xing Liu (2022) suggests that AI-based English network teaching (AI-ENT) is an effective strategy for improving students' outcomes while taking courses online [25]. There are signs that AI has the potential to radically revolutionize both the means of education and the instruments used for instruction in machine learning.…”
Section: Related Workmentioning
confidence: 99%
“…Tis article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. Tis investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%